Differrences in The Meaning Dolalak Dance in PurworejoDistrick, Central Java Province - Adeliana Galih Nurbaidhah; Nurhadi Nurhadi; Sigit Pranawa (Jurnal Ilmu Sosial Mamangan, 2020)
Dolalak dance is a folk dance whose movements and costumes adopted the Dutch soldiers war training and dancing movements and costumes. The exsistention of the traditional art become degradation in a year. Dolalak dance is also influenced by the cultural change from modernity, and then the meaning of Dolalak will be gone.This enable people interprete the ideal value of Dolalak dance in daily life that different from Dolalak dance in the past that was full of life regulation values.This qualitative research uses a case study method to answer the different interprete the meaning of Dolalak dance.It uses interview, observation and documentation techniques to collect data. Theory in thisresearch using interpretative culture from Clifford Geertz.This research reveals that Dolalak experienced a cultural creativity by combining with other arts, i.e dangdut and Campursari.It also experienced changes in players, movements, makeup, costumes, and time performanes. As a folk dance play a role in unity and guide the social life. Dolalak dance is interpreted as a religious symbols, varlour, faith and social conditions. Nowdays, it has a new interpretation as a equality, effectivity, efficiency and specialization lead to individualization in the group.